Data and two-dimensional scaling relations for galaxies in Abell 1689: a hint of size evolution at z similar to 0.2 - Houghton, R; Davies, R; Dalla Bonta, E; Masters, R (2012)
We present imaging and spectroscopy of Abell 1689 (z= 0.183) from the Gemini multi-object spectrograph (GMOS) on the Gemini North telescope and the Advanced Camera for Surveys (ACS) on the Hubble Space Telescope (HST). We measure integrated photometry from the GMOS g' and r' images (for 531 galaxies) and surface photometry from the HSTF625W image (for 43 galaxies) as well as velocities and velocity dispersions from the GMOS spectra (for 71 galaxies). We construct the Kormendy, Faber-Jackson and colour-magnitude relations for early-type galaxies in Abell 1689 using these data and compare them to those of the Coma cluster. We measure the intrinsic scatter of the colour-magnitude relation in Abell 1689 to be σ CMR= 0.054 ± 0.004mag, which places degenerate constraints on the ratio of the assembly time-scale to the time available (β) and the age of the population. Making the assumption that galaxies in Abell 1689 will evolve into those of Coma over an interval of 2.26Gyr breaks this degeneracy and limits β to be >0.6 and the age of the red sequence to be >5.5Gyr (formed at z > 0.55). Without corrections for size evolution but accounting for magnitude cuts and selection effects, the Kormendy and Faber-Jackson relations are inconsistent and disagree at the 2σ level regarding the amount of luminosity evolution in the last 2.26Gyr. However, after correcting for size evolution the Kormendy and Faber-Jackson relations show similar changes in luminosity (0.22 ± 0.11mag) that are consistent with the passive evolution of the stellar populations from a single burst of star formation 10.2 ± 3.3Gyr ago (). Thus, the changes in the Kormendy, Faber-Jackson and colour-magnitude relations of Abell 1689 relative to Coma all agree and suggest old galaxy populations with little or no synchronization in the star formation histories. Furthermore, the weak evidence for size evolution in the cluster environment in the last 2.26Gyr places interesting constraints on the possible mechanisms at work, favouring harassment or secular processes over merger scenarios. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.